Penyuluhan Pencegahan Stunting dalam Upaya Meningkatkan Kewaspadaan Ibu Terhadap Permasalahan Tumbuh Kembang Anak di Posyandu Kelurahan Nyapah Kecamatan Walantaka - Diana Romdhoningsih; Mahpudoh Mahpudoh; Aziz Fahmi; Arnawati Arnawati; R. Bilqis Ratu Nirwana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Stunting is a child's height shorter than a child's height. In Indonesia, stunting's case continues to be a considerable number of health problems because of chronic undernourishment and faltering growth that begins from gestational to 2 years old because of our need to have a stunning program, especially in lives, which is the Walantaka district . This article aims to provide information on stunting prevention to children that most national development students have done through counseling methods in cooperation with the local community center to bring information to the public to bring people through a public health movement. This method is thus very effective in providing information on preventing and reducing stunting events in children. His hope was with his stunting marriage counseling key. Walantaka's awareness of growing children's development is increasingly noted to prevent stunting and lower stunting rates in Indonesia, especially in the Nyapah Villages in Walantaka subdistrict